A Review on Advancements in Braking Systems in Auto Motive Industry - Manikandan, J.; Raghavendra Reddy, B. (International Journal of Psychosocial Rehabilitation, 2019)
The paper mainly discusses the brake systems, which are being updated these days. It also explains in detail the necessity of upgrading the systems and the factors that are influencing the changes, like road conditions, etc. The braking systems should always be in upgraded form so as to ensure passenger safety. It mainly shows the process of some of the advanced braking systems.